PENGARUH EARNING PER SHARE, NET PROFIT MARGIN DAN ARUS KAS OPERASI TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Syaiful, Syaiful; Afrida (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
The share price is the price set for a company for other parties who want to have ownership rights to a company through shares. The research aims to examine the influence of EPS, NPM, and Operating Cash Flow on Stock Prices. This type of research is quantitative descriptive. The sampling method in this research used a purposive sampling method. The samples used were 16 of the 30 Food and Beverage companies on the Indonesian Stock Exchange for the 2018-2022 period. The data used is secondary data. The analytical method used is multiple linear regression analysis using the SPSS program. Based on the results of hypothesis testing carried out in this research, it can be concluded that partially Earning Per Share has a positive and significant effect on Share Prices with a calculated T value of 7.713 > T table 1.703 and a significant of 0.000 which is smaller than 0.05, so hypothesis H1 can be accepted . Net Profit Margin has a significant effect on share prices with a calculated T value of 5.284 > T table 1.703 and is significant at 0.000, less than 0.05, so hypothesis H2 can be accepted. Operating Cash Flow has a positive but not significant effect on share prices, with a calculated T value of 1.801 > T table 1.703 and a significant value of 0.076 which is greater than 0.05, so hypothesis H3 is rejected. Earning Per Share, Net Profit Margin, and Operating Cash Flow simultaneously have a positive and significant effect on share prices, with a calculated F value of 52.325 > F table 2.98, and a significant 0.000 smaller than 0.05, so hypothesis H4 can be accepted. The influence of Earning Per Share (X1), Net Profit Margin (X2), and Operating Cash Flow (X3) on Share Prices (Y). The coefficient of determination written R Square is 0.707. It can be explained that the large proportion of influence of Earning Per Share, Net Profit Margin and Operating Cash Flow on Share Price (Y) is 70.7%, while the remaining 29.3% is influenced by other factors outside the variables used in this research.